2006
DOI: 10.1111/j.1365-2338.2006.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Prunus/Plum pox virus interactions

Abstract: Plum pox virus (PPV) belongs to the genus Potyvirus that contains the largest number of virus species infecting plants. Its virus genome has been extensively characterised and sequenced. However, few data are available on its interactions with woody host plants. We therefore focused, in the past 4 years, both on the cellular and molecular aspects of the compatible and incompatible Prunus /PPV interactions. GFP (Green fluorescent protein)-tagged PPV and in situ hybridisation were used to compare the localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…2). Indeed, when ‘Stark Early Orange’ was challenged with eight distinct PPV isolates, no difference in resistance level was observed (Decroocq et al ., 2006a). We can therefore hypothesize that these QTLs and, consequently, the metaQTLs display a broad‐spectrum range of resistance to PPV, suggesting that a conserved viral determinant may be recognized by the plant.…”
Section: Discussionmentioning
confidence: 99%
“…2). Indeed, when ‘Stark Early Orange’ was challenged with eight distinct PPV isolates, no difference in resistance level was observed (Decroocq et al ., 2006a). We can therefore hypothesize that these QTLs and, consequently, the metaQTLs display a broad‐spectrum range of resistance to PPV, suggesting that a conserved viral determinant may be recognized by the plant.…”
Section: Discussionmentioning
confidence: 99%
“…No systemic PPV infection was detected in the scion of 'Stark Early Orange' inoculated with eight different PPV isolates, corresponding to the three major serotypes 'Marcus', 'Dideron' and 'El Amar' in a six-year study (Decroocq et al 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Silencing or mutation of host factors required for virus infection will generate genetic resistance to the virus. Over the last decade, a number of host factors required for potyvirus infection have been identified and examples include eIF4E, eIF(iso)4E, eIF4G, PABP, AtRH8 and PpDDX (Lellis et al, 2002;Ruffel et al, 2002Ruffel et al, , 2005Nicaise et al, 2003Nicaise et al, , 2007Gao et al, 2004;Kang et al, 2005;Decroocq et al, 2006;Bruun-Rasmussen et al, 2007;Dufresne et al, 2008;Huang et al, 2010). Recently Piron et al (2010) have reported a successful story about how to deploy host factors for the development of resistance to potyviruses in tomato.…”
Section: Novel Strategies To Control Smvmentioning
confidence: 99%